Molecular engineering of D-A-π-A dyes with 2-(1, 1-dicyanomethylene)rhodanine as an electron-accepting and anchoring group for dye-sensitized solar cells. (10th October 2015) - Mao, Jiangyi; Zhang, Xiaoyu; Liu, Shih-Hung; Shen, Zhongjin; Li, Xing; Wu, Wenjun; Chou, Pi-Tai; Hua, Jianli
Graphical abstract: We designed and synthesized two new D-A-π-A dyes (RD-III andRD-IV ) with 2-(1, 1-dicyanomethylene) rhodanine (DCRD) as an electron-accepting and anchoring group. The theoretical calculation of dye/(TiO2 )38 displayed that the angle between the molecule ofRD-III and the surface of TiO2 was only 31.84 0 in contrast to 97.16 0 forCA-III . This adsorption state can facilitate dye aggregation and charge recombination, resulting in a decrease of short circuit current density ( J sc ) and open circuit voltage ( V oc ). Further improvement has been successfully made by adding long alkoxy chains with large steric hindrance. After introducing the alkoxy chains of the benzothiadiazole unit, the dihedral angle betweenRD-IV and TiO2 increased to 42.61 0 and the steric hindrance can inhibit dye aggregation and charge recombination. Therefore, higher photoelectric conversion efficiency of 5.53% was obtained withRD-IV in DSSC devices compared with 4.51% for DSSC based onRD-III . Highlights: We obtained two D-A-π-A dyes with 2-(1, 1-dicyanomethylene) rhodanine as acceptor. Introduction of octyloxy groups can increase the angle of dye/TiO2 . Octyloxy groups can inhibit dye aggregation and charge recombination effectively. Higher power conversion efficiency of 5.53% was obtained with dye octyloxy group. Abstract: The electron-accepting and anchoring group plays a significant role on the optical and electrochemical properties of an organic dye. They also affect the intramolecular charge transfer, the electron injection processes and the adsorption mode, hence the photostability of the dye on TiO2 films. In this study, we have designed and synthesized two new D-A-π-A dyes (RD-III andRD-IV ) with 2-(1, 1-dicyanomethylene) rhodanine (DCRD) as electron-accepting and anchoring group. For comparison, an analogue ofRD-III, namelyCA-III, with cyanoacrylic acid (CA) as the acceptor was also prepared. We have carefully examined their optical and electrochemical properties, device performance and electrochemical impedance spectroscopy (EIS). Supplementary support is given by computational approach to gain in-depth insight into the adsorption states and electron contributions. The theoretical calculation of dye/(TiO2 )38 displayed that the angle between the molecule ofRD-III and the surface of TiO2 was only 31.84 0 in contrast to 97.16 0 forCA-III . This adsorption state can facilitate dye aggregation and charge recombination, resulting in a decrease of short circuit current density ( J sc ) and open circuit voltage ( V oc ). Further improvement has been successfully made by adding long alkoxy chains with large steric hindrance. After introducing the alkoxy chains, the dihedral angle betweenRD-IV and TiO2 increased to 42.61 0 and the steric hindrance can inhibit dye aggregation and charge recombination. Therefore, higher photoelectric conversion efficiency of 5.53 % was obtained withRD-IV in DSSC devices compared with 4.51 % for DSSC based onRD-III .